The Dermal Papilla: An Instructive Niche for Epithelial Stem and Progenitor Cells in Development and Regeneration of the Hair Follicle - Morgan, Bruce A. (Cold Spring Harbor Laboratory Press, 2014)
The dermal papilla (DP) of the hair follicle is both a chemical and physical niche for epithelial progenitor cells that regenerate the cycling portion of the hair follicle and generate the hair shaft. Here, we review experiments that revealed the importance of the DP in regulating the characteristics of the hair shaft and frequency of hair follicle regeneration. More recent work showed that the size of this niche is dynamic and actively regulated and reduction in DP cell number per follicle is sufficient to cause hair thinning and loss. The formation of the DP during follicle neogenesis provides a context to contemplate the mechanisms that maintain DP size and the potential to exploit these processes for hair preservation or restoration.